Implementation of the Guided Discovery Learning Model Assisted by Parachute Teaching Aids on the Material of Relationships Between Angles - Sari, Annisa Kurnia; Tandililing, Pitriana Yohanes; Sirampun, Elsi; Lumbantobing, Happy; Ruamba, Marthinus Yohanes (JUPE : Jurnal Pendidikan Mandala, 2025)
This research is a descriptive qualitative research. The subjects of this research were 31 students of class VII A of SMP YPPK Santu Paulus Abepura. The selection of subjects used the purpose sampling technique. The research instruments used were individual tests, teacher observation sheets and student observation sheets. This study aims to describe the implementation of the guided discovery learning model on the material of relationships between angles assisted by parachute teaching aids (line and angle boards) in class VII A of SMP YPPK Santu Paulus Abepura. Based on the results and discussion of the learning process by applying the guided discovery learning model on the material of the relationship between angles assisted by parachute teaching aids (line and angle boards) has gone very well. This is shown in the results of observations and individual tests falling into the very good category with the percentage of teachers in applying the guided discovery learning model of 97.89%, student activity of 94.21%, and an average individual test score of 92.74. By applying the guided discovery model to the material of the relationship between angles assisted by parachute teaching aids, students can become active and motivated in participating in mathematics learning.